Population biology of the hermit crab Petrochirus diogenes (Linnaeus) (Crustacea, Decapoda) in Southern Brazil - Turra,Alexander (2002)
The aim of this study was to provide information on the biology of a subtropical population ofthe hermit crab Petrochirus diogenes focusing size structure, sex ratio, reproductive period and morphometric relationships. Monthly samples were done between January and December 1995 at Armação of Itapocoroy, Penha, southern Brazil, using two over-trawls in depths from 6.0 to 10.0 m. A total of 126 individuais were collected. Overall sex ratio did not differ from 1:1. When the sex ratio was analyzed for each size class, it was skewed for females in the smallest size classes while males outnumbered females in the largest ones. The mean size (cephalothoracic length) of P. diogenes was 30.61 ± 12.52 mm and the size structure of this population was skewed to the right. Males were on average larger and heavier than both ovigerous and non-ovigerous females, which, in turn, showed similar sizes and weights. The ovigerous females represented 61% ofall females and occurred from January to April and in September and December. The relationship of cephalothoracic length and both cephalothoracic width and crab weight were isometric. Both crab size and weight showed a negative allometry with shell weight, indicating that larger/heavier crabs use proportionally lighter shells than small-sized ones.